2013
DOI: 10.1590/s1519-99402013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Métodos de análise da cinza insolúvel em ácido utilizada como indicador na determinação da energia metabolizável do milho para aves

Abstract: Objetivou-se avaliar métodos de análise da cinza insolúvel em ácido como indicador na determinação da energia metabolizável do milho para aves em relação ao procedimento padrão de coleta total de excretas. Foi formulada uma dieta referência a base de milho e farelo de soja e uma dieta teste com inclusão de 40% de milho à dieta referência. Foi adicionado 1% de celite™ às dietas, como fonte de cinza insolúvel em ácido. Foram utilizados 60 pintos de corte, da linhagem Cobb500, dos 12 aos 21 dias de idade, distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…To determine the gross energy ( GE ), samples were subjected to combustion in a calorimetric pump (IKA C200 IKA Werke GmbH & Co.Kg, Staufen, BW, DE). To determine the indigestibility factor, an analysis of acid insoluble ash ( AIA ) was performed, according to the methodology described by Van Keulen and Young (1977) and adapted by Carvalho et al (2013) . Using the results obtained from diets and digesta, total digestible nutrients were determined: acid insoluble ash ( digAIA ), digestible crude protein ( digCP ), digestible crude energy ( digCE ), digestible ash ( digAsh ), and digestible dry matter ( digDM ).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the gross energy ( GE ), samples were subjected to combustion in a calorimetric pump (IKA C200 IKA Werke GmbH & Co.Kg, Staufen, BW, DE). To determine the indigestibility factor, an analysis of acid insoluble ash ( AIA ) was performed, according to the methodology described by Van Keulen and Young (1977) and adapted by Carvalho et al (2013) . Using the results obtained from diets and digesta, total digestible nutrients were determined: acid insoluble ash ( digAIA ), digestible crude protein ( digCP ), digestible crude energy ( digCE ), digestible ash ( digAsh ), and digestible dry matter ( digDM ).…”
Section: Methodsmentioning
confidence: 99%
“…Some fecal collection methods have been used to determine the digestibility of the nutrients and energy of feeds for monogastric animals. Among these methods are the total collection and the use of fecal indicator (acid insoluble ash, AIA); however, the respective obtained data are still contradictory (CARVALHO et al, 2013). Determining the digestibility by the traditional method of total excreta collection requires strict control of the intake and excretion, which causes this work to be costly (CARVALHO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods are the total collection and the use of fecal indicator (acid insoluble ash, AIA); however, the respective obtained data are still contradictory (CARVALHO et al, 2013). Determining the digestibility by the traditional method of total excreta collection requires strict control of the intake and excretion, which causes this work to be costly (CARVALHO et al, 2013). Thus, the objective of this study was to determine the apparent and standardized digestibility coefficients of phosphorus according to the phosphate particle sizes by applying two simultaneous methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, excreta and feed samples were ground and sent to the laboratory for determination of dry matter, crude energy, and nitrogen contents according to D. J. Silva and Queiroz (2002), and insoluble acid ash using a methodology adapted from Carvalho et al (2013). The results obtained were used to calculate the apparent metabolizable energy (AME) values, according to the formulas described by Sakomura and Rostagno (2016).…”
mentioning
confidence: 99%
“…Researchers are yet to find a substance with a perfect indicator feature. However, Carvalho et al (2013) showed that partial collection with marker method is comparable to the standard procedure of total collection of excreta, indicating that acid insoluble ash (AIA) can be used as a marker to predict the AME and digestibility coefficients of ingredients, as they present similar results.…”
mentioning
confidence: 99%